1994
DOI: 10.2105/ajph.84.12.2000
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection, risk behaviors, and depressive symptoms among Puerto Rican sex workers.

Abstract: This paper examines the association of depressive symptoms with human immunodeficiency virus (HIV) infection and risk behaviors among 127 sex workers. Data were obtained by a structured interview and blood specimens tested for HIV. Findings showed a high prevalence rate of depressive symptoms for all sex workers regardless of HIV infection status. Results of a logistic regression analysis indicated that the use of injected drugs and engaging in unprotected intercourse with clients were strongly associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
92
4
4

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 18 publications
5
92
4
4
Order By: Relevance
“…Western nations, several studies have reported significant associations between depression and HIV risk behaviors among high risk populations (Alegria et al, 1994;Perdue et al, 2003). The results from our study support the relationship between depression and involvement in commercial sex, although we are not able to determine the causality between them, given the nature of cross-sectional data.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Western nations, several studies have reported significant associations between depression and HIV risk behaviors among high risk populations (Alegria et al, 1994;Perdue et al, 2003). The results from our study support the relationship between depression and involvement in commercial sex, although we are not able to determine the causality between them, given the nature of cross-sectional data.…”
Section: Discussioncontrasting
confidence: 51%
“…Although providing valuable information about HIV risk behaviors and condom use, these studies did not include comparison groups. In addition, most of these studies did not examine psychosocial factors such as depression and peer risk involvement, which have been found to be related to risk behaviors in western nations (Alegria, Vera, Freeman, Robles, Santos, & Rivera, 1994;Perdue, Hagan, Thiede, & Valleroy, 2003;Simpson, Knight, & Ray, 1993). The current study, comparing female migrants who had engaged in commercial sex with female migrants who had not engaged in commercial sex, therefore, was designed to (1) examine the sociodemographic characteristics of female migrants engaging in commercial sex; (2) explore their HIV-related risk behaviors and perceptions; and (3) explore the association between depression and involvement in commercial sex.…”
mentioning
confidence: 99%
“…Global literature suggests that, compared with the general population, FSWs generally have relatively higher rates of psychopathology and other health-related risks, including higher rates of depressive symptoms, drug use, and psychological distress (Alegria et al, 1994;El-Bassel et al, 1997;El-Bassel, Witte, Wada, Gilbert, & Wallace, 2001,Jones et al, 1998Surratt, Kurtz, Weaver, & Inciardi, 2005). Only limited data are available regarding self-destructive behaviors such as suicide among the FSW population.…”
Section: Introductionmentioning
confidence: 99%
“…O BDI foi extensamente validado em amostras clínicas e populacionais brasileiras por Cunha e colaboradores 8 , que encontrou os seguintes pontos de coorte para diferentes intensidades dos sintomas depressivos: míni-mo (0-11), leve (12)(13)(14)(15)(16)(17)(18)(19), moderado (20-35) e grave (36 a 63).…”
Section: Methodsunclassified